Building Blocks for a Better Functioning Housing Market in Chile - Caldera Sánchez, Aida (OECD Publishing, 2012)
Chile has made good progress in improving housing conditions, but still around 10% of the population lives in either overcrowded houses, or of inadequate quality and/or with poor access to basic services. Improving further housing conditions of the poor is important for curbing poverty and reducing inequality. First, better targeting of housing subsidies will be essential to free resources for those truly in need. The government should also rethink subsidies, which are currently directed exclusively at ownership. Means-tested rental cash allowances coupled with more balanced tenant-landlord regulations would strengthen the rental market, thus enhancing residential mobility and potentially reducing segregation. Second, better enforcement of social housing quotas for new building projects coupled with investments in urban renewal and social services in poorer neighbourhoods and developing unused land in urban areas could also help to reduce inequalities. Third, effective thermal and energy standards for buildings would improve the quality of the housing stock, protect public health and reduce air pollution. Limiting construction in fault lines and risky coastal areas could also increase Chile's resilience to natural disasters. Fourth, taxing housing so owing is not favoured over renting would reduce distortions and make the tax system less regressive. Finally, enhancing the responsiveness of housing supply to demand would ensure there is a good match between housing construction and demand, and avoid that public support gets capitalised into housing prices
Keywords: Economics; Chile